14. RELIABILITY AND VALIDITY OF KOREAN STANDARD PATTERN IDENTIFICATION FOR STROKE III VIETNAMESE VERSION (Vietnam Journal of Community Medicine, 2025)
Objective: Vietnamese traditional medicine uses the syndrome diagnosis method to diagnose stroke, but there is still no standardized tool. The Korean K-SPI-Stroke III scale provides a solution; therefore, its feasibility for application in Vietnam needs to be evaluated due to differences in culture and physical characteristics.Subject and methods: A two-phase study was conducted. Phase 1 translated and culturally adapted K-SPI-Stroke III into Vietnamese, assessing content validity (I-CVI and S-CVI: 100%; clarity I-CVI: 80-100%, S-CVI/Ave: 99%, S-CVI/UA: 96%) and face validity. Phase 2 evaluated reliability and validity with 66 stroke patients.Results: Internal consistency (Cronbach’s alpha: 0.78-0.84) and test-retest reliability (question kappa: 0.43-0.86; sub-scale correlations: 0.76-0.94) were strong. Discriminant validity showed significant score differences among patterns, with predictive value at 62.1%.Conclusion: The Vietnamese K-SPI-Stroke III demonstrates robust reliability and validity, supporting its use in traditional stroke diagnosis research in Vietnam
Keywords: K-SPI-Stroke III; reliability; validity.